Knowledge, Attitudes, and Clinical Implementation of Pressure Injury Prevention among Intensive Care Nurses - Akmala Dewi, Nur; Kholid Rosyidi Muhammad Nur; Ikha Nurjihan; Masmuhul Khoir (KHD Production, 2026)
Pressure ulcers represent a significant patient safety concern in intensive care units, primarily due to prolonged immobilization, impaired tissue perfusion, and the use of invasive medical devices. Nurses play a pivotal role in prevention through adequate knowledge and positive attitudes toward evidence-based interventions. This study described nurses' knowledge and attitudes regarding pressure ulcer prevention in the Melati Intensive Care Unit at Bangil Regional General Hospital. A descriptive design with purposive sampling was employed, involving three intensive care nurses as respondents. Data collection utilized validated instruments: the Pressure Ulcer Knowledge Assessment Tool (PUKAT) and the Attitude Towards Pressure Ulcer Prevention Instrument (APuP). Descriptive statistical analysis presented findings through frequency and percentage distributions. Results indicated that 66.7% of nurses demonstrated adequate knowledge, 33.3% demonstrated good knowledge, and no respondents exhibited poor knowledge. All respondents (100%) displayed positive attitudes toward pressure ulcer prevention and consistently implemented preventive measures in accordance with standard operating procedures. These findings suggest that nurses possess sufficient cognitive and affective competencies to support effective pressure ulcer prevention practices, including regular repositioning, maintenance of skin integrity, moisture management, and comprehensive risk assessment. The alignment between adequate knowledge, positive attitudes, and optimal implementation reflects a strong patient safety culture within the intensive care unit. However, the lack of formal specialized training among most respondents underscores the need for structured continuing education programs. Institutional support for regular training is essential to maintain evidence-based practice standards and ensure sustainable quality improvement in pressure ulcer prevention, ultimately enhancing patient safety outcomes in critical care environments.